Analisis Penggunaan Bahasa dan Ejaan pada Media Sosial X Yupienfess - Sabrina Jennifer Loren Alexandria; Bernadeta Dian; Nimas Nuraini; Aisyah Shella M; Reza Febri A (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Analysis of Language Usage and Spelling on Social Media X Yupienfess is one of the scientific papers compiled by us. X Yupienfess is a menfess platform used by three campus branches, namely UPN Jakarta, Yogyakarta, and Surabaya. Our group is interested in analyzing the use of language used by users of the platform. Menfess itself is a message delivered anonymously. This study uses a qualitative method as a research approach. The data collection technique used is observation of language use and documentation in the form of screenshots to be used as the subject of analysis. The data analysis technique used in this study is semantic analysis, which focuses on the meaning of words in language. The object of this study is the X Yupienfess platform. Based on the results of the study, it was found that X Yupienfess users use a lot of slang, a mixture of foreign languages, and regional languages.